Nipple viability after nipple‐sparing mastectomy in patients with prior circum‐areolar incisions. Issue 6 (31st July 2018) - Rose, Jessica F.; Zavlin, Dmitry; Lim, Sherry J.; Spiegel, Aldona J.; Chevray, Pierre M.; Albright, Steven B.; Friedman, Jeffrey D.
Abstract: Nipple‐areola‐sparing mastectomy (NSM) is becoming more commonplace as it offers a more esthetic breast appearance while still appropriately treating malignancy. However, patients with prior circum‐areolar incisions are often considered at risk for nipple viability. The authors present a case series of all patients undergoing NSM at their institution between 2012 and 2016. Eighteen consecutive female nonsmoking patients underwent 32 NSMs. None of the patients had reconstructive failures including those relating to the nipple‐areola complex (NAC), such as nipple necrosis. NSM is therefore feasible in cases with prior circum‐areolar incisions. These patients can be safely reconstructed with both prosthetic devices and autologous tissue.